Tinjauan Fiqh Siyasah Syar’iyyah Terhadap Peran Pemimpin Perempuan Dalam Sistem Ketatanegaraan Di Kecamatan Medan Tembung - Ortata, Klara; Pasaribu, Kristin; Dinda , Sinvani; Assiddiq, Yusuf; Putra, Aldris (Tabayyun : Journal Of Islamic Studies, 2023)
Women are often the targets of public anger. The role of women in society is not only as a development process, but also as a strong structural foundation. A leader is a person who rules an area. Managers must have a leadership spirit when moving around the environment. The results of the study show that leaders in Medan Tembung District, Medan City are dedicated to providing services and work policies that are in line with the vision and mission in Medan Tembung District, especially for electronic services that offer electronic support. Free electronic services are available from Feel in the center of Medan City to make it easier for the general public to get services that are timely, efficient and in accordance with Siyasah syar'iyyah quotations. It has value both in the world and in Islam